Effect of β-adrenergic receptor agents on cardiac structure and function and whole-body gene expression in Daphnia magna. (October 2018) - Jeong, Tae-Yong; Asselman, Jana; De Schamphelaere, Karel A.C.; Van Nieuwerburgh, Filip; Deforce, Dieter; Kim, Sang Don
Abstract: Propranolol (PRO), a human β-AR (β-adrenergic receptor) antagonist, is considered to result in specific effects in a non-target species, D. magna, based on our previous studies. The present study investigated the effects of β-AR agents, including an antagonist and agonist using pharmacologically relevant endpoints as well as a more holistic gene expression approach to reveal the impacts and potential mode of actions (MOAs) in the model non-target species. Results show that the responses in cardiac endpoints and gene expression in D. magna are partially similar but distinguishable from the observations in different organisms. No effect was observed on heart size growth in PRO and isoprenaline (ISO) exposure. The contraction capacity of the heart was decreased in ISO exposure, and the heart rate was decreased in PRO exposure. Time-series exposures showed different magnitudes of effect on heart rate and gene expression dependent on the type of chemical exposure. Significant enrichment of gene families involved in protein metabolism and biotransformation was observed within the differentially expressed genes, and we also observed differential expression in juvenile hormone-inducible proteins in ISO and PRO exposure, which is suspected of having endocrine disruption potential. Taken together, deviation between the effects of PRO and ISO in D. magna and other organisms suggests dissimilarity in MOAs or attributes of target bio-molecules between species. Additionally, PRO and ISO may act as endocrine disruptors based on the gene expression observation. Results in the present study confirm that it is challenging to predict ecological impact of active pharmaceutical ingredients (APIs) based on the available data acquired through human-focused studies. Furthermore, the present study provided unique data and a case study on the impact of APIs in a non-target organism. Graphical abstract: Highlights: Long- and short-term effects of β-adrenergic antagonist and agonist on D. magna were studied. Six-day exposure to isoprenaline and propranolol reduced heart contraction capacity and heart rate, respectively. Gene expression analysis propose potential modes of actions, including endocrine disruption. Study results suggest differential effects on heart function and whole body gene expression in Daphnia magna . Abstract : Present study reveals that effects of β-adrenergic agents on heart function and gene expression of Daphnia magna are distinguishable from effects on other species despite partial similarity.